Effect of changing electronic states of molecules on frequency domain of graphene FETs. (1st April 2022) - Oketa, Tomohiro; Ikuta, Takashi; Masai, Hiroshi; Tamaki, Takashi; Terao, Jun; Maehashi, Kenzo
Abstract: The high surface sensitivity of low-dimensional carbon nanomaterials renders them good candidates for noise detection. Herein, Mg-porphyrin-modified graphene field-effect transistors (FETs) were fabricated, and parts-per-billion concentrations of NO2 were introduced to the devices. When the power spectrum density (PSD) of the Mg-porphyrin-modified graphene was measured in NO2, a specific PSD change near 1000 Hz was observed. This change could be due to the change in the electrical state of Mg-porphyrin caused by NO2 adsorption. This study reveals that frequency-domain measurement of graphene FETs can be used to evaluate changes in the electronic state of molecules.